Turbo BEM OTFS Receiver with Optimized Superimposed Pilot Power - Liu, Yujie; Guan, Yong Liang; Gonzalez G., David (IEEE transactions on communications, 2024)
In this paper, a Turbo basis expansion modeling (BEM) orthogonal time frequency space (OTFS) scheme is proposed for high-mobility communications subject to either Doppler-shift or Doppler-spread channel. It consists of super-imposed pilot power and BEM order optimization and Turbo BEM OTFS receiver. The signal-to-interference-and-noise ratio (SINR) is derived as functions of OTFS system parameters and several channel information (i.e., channel correlation matrix, noise variance, etc.). The optimal superimposed pilot power ratio is then derived with a closed-form solution by calculating the first derivative of derived SINR. BEM order is specially optimized for each channel, instead of simply increasing or reducing it. The Turbo BEM OTFS receiver is proposed with an exchange of soft information between BEM channel estimation, signal detection, and data decoding, leading to high reliability. By using superimposed pilots for initial BEM channel estimation, the proposed Turbo BEM OTFS scheme has zero dedicated pilot overhead, resulting in high spectral efficiency. Simulation results confirm that the proposed OTFS scheme outperforms the existing OTFS schemes in terms of bit error rate (BER) and spectral efficiency. Extrinsic information exchange transfer (EXIT) chart analysis and simulation results also exhibit the fast convergence speed of proposed OTFS scheme.